Photocatalytic decolorization of methylene blue in the presence of TiO2/ZnS nanocomposites - Franco, A. (2012)
The synthesis of distinct nanocrystalline TiO2 capped ZnS sampleswas carried out using a chemical deposition method. The materials characterization showed that the presence of ZnS onto TiO2 surface results in a red shift of the material band edge when compared with the initial semiconductor. The photocatalytic activity of the prepared nanocomposites was tested on the decolorization of methylene blue (MB) aqueous solutions. The dye photodecolorization processwas studied considering the influence of experimental parameters such as catalyst concentration, TiO2/ZnS ratio, pH and methylene blue adsorption rate. The material with the best catalytic activity towards the methylene blue photodecolorization was the TiO2 doped with 0.2% of ZnS. The complete photodecolorization of a 20ppmmethylene blue solution, at natural pH was achieved in less than 20 min, nearly 70 min faster than the TiO2 photoassisted process.